The Influence of Discipline and Achievement on the Work Commitment of Teachers of Ibtidaiyah Madrasah State 4 East Aceh - Usman Usman; Zainuddin Zainuddin; Rita Sari (IAIN Padangsidimpuan, 2021)
The purpose of the study to describe three things, namely the partial influence of discipline on work commitments, the partial influence of achievement on work commitments, and the simultaneous influence of work commitments of teacher madrasah Ibtidaiyah Negeri 4 Aceh Timur. The research method used is quantitative survey. Collecting data using questionnaires. Data analysis is performed with regression test, t test, F test, and determination coeffesient. The findings showed that there was a partial influence of disciplinary variables on work commitments of 0.319 (31%), there was a partial influence of achievement on work commitments of 0.594 (59%) and there is a simultaneous influence of discipline and achievement together on teacher work commitments of 0.940 (94%) only 6% were affected by other variables outside of this study